Prejudices, annoyances and rejections: music territorialities and conflicts in contemporary Brazil - Trotta, Felipe (2018)
Music is an important artefact that helps people to construct identities and territorial links, establishing shared imaginaries and symbols that, on their turn, structure ideas about places such as neighbourhoods, cities, and nations. At the same time, music marks distinctions between them, mostly through negative feelings; rejections and prejudices against genres and territories. In this article, the cases of Brazilian genres samba, forró and sertanejo are analysed, taking them as markers of specific territories and spaces in the nation’s hierarchies. Therefore, they can be thought as agents of music conflicts which are intermingled with symbolic and geographic struggles.